2015
DOI: 10.1007/s13762-015-0892-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-contaminated soil mixtures as fixed/fluidized bed media on pollutants emission under thermal treatment

Abstract: Thermal treatment of soil polluted by lube oil and heavy metals (cadmium, chromium, copper, and lead) was carried out by using a laboratory-scale incinerator. The effect of co-contaminated soil mixtures as fixed/fluidized bed media was studied with different ratios of sand bed amount to soil feeding. Additionally, the effect of soil moisture content on incineration system was further investigated. The reduction in air input altered the mode of fluidized bed to fixed bed which resulted in an increase in organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…Fluidized-bed reactors can provide high heating rates and shorten the time lag of devolatilization, but the particle dispersion causes very slight or no interactions (Samaksaman et al, 2016). In this work, a drop-tube reactor is used to perform fast pyrolysis experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Fluidized-bed reactors can provide high heating rates and shorten the time lag of devolatilization, but the particle dispersion causes very slight or no interactions (Samaksaman et al, 2016). In this work, a drop-tube reactor is used to perform fast pyrolysis experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Residual TPH in all treatments decreased with treatment time, and the removal rates increased with treatment temperature. Generally, the addition of sand to OBDCs improved the desorption rates of TPH, which is in agreement with Samaksaman et al (2016a) who showed that a ratio of sand/soil (0.75/1 to 1.5/1) could enhance the elimination of BTEX and PAHs in both fixed bed and fluidized bed reactors.…”
Section: Kinetics Of Tph Removal From Obdcs Treated With Lttdsupporting
confidence: 90%
“…In this study, the LTTD treatment of OBDCs artificially spiked with different PHCs content was examined using a bench-scale apparatus. Ottawa sand was mixed with OBDCs with different mixing ratios to enhance the LTTD remediation process, as the additive could improve the texture and pore size of drill cuttings, thus increasing the effective diffusivity in porous media (Falciglia et al, 2011, Samaksaman et al, 2016a. The main objectives of the study were: (1) to analyze the changes of soil properties before and after thermal treatment, and examine the impacts of LTTD process on soil characteristics;…”
Section: List Of Figuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Petroleum hydrocarbons (PHCs) and heavy metals are potential persistent environmental toxins (Roy et al, 2005). They could exist at contaminated sites affected by accidental spills and leaks from petroleum, transportation, and mining industries (Samaksaman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%